Emotional Leakage in Everyday School Interactions: A Descriptive Study of Grade VI Students - Timothy Jacob; Fitriah Assagaff (Universitas Negeri Medan, 2026)
Hidden emotional struggle is often difficult to identify in school settings because students may present themselves as calm, happy, or socially functional while still experiencing discomfort, stress, or unexpressed emotion. This study examined how small behaviours and body language may reveal hidden emotional struggle in everyday social interaction among peers through the theoretical lens of Paul Ekman’s concept of emotional leakage. Using a descriptive quantitative design, data were collected through a seven-item Google Forms questionnaire administered to 20 Grade VI students at Cendekia Harapan School over two days. The survey focused on students’ observations of incongruent emotional presentation, their attention to subtle nonverbal cues, their own experiences of hiding emotion, and their views about the mental-health effects of prolonged concealment. The findings showed that 70% of participants had seen someone appear happy while seeming nervous or uncomfortable, 75% reported having hidden their own emotions, and 95% believed that hiding emotions for too long can affect mental health. These findings suggest that students already recognize nonverbal signs of emotional incongruence in daily life. The study contributes a school-based descriptive account of how emotional leakage is perceived by children and argues for emotionally supportive, non-diagnostic approaches to social-emotional learning in primary education.